Combined MSC-Secreted Factors and Neural Stem Cell Transplantation Promote Functional Recovery of PD Rats. Issue 6 (June 2016) - Yao, Yuan; Huang, Chen; Gu, Ping; Wen, Tieqiao
Stem cell transplantation has enormous potential for the treatment of neurodegenerative disorders like Parkinson's disease (PD). Mesenchymal stem cells (MSCs) have attracted much attention because they can secrete a wide variety of cellular factors that promote cell growth. In this study, we prepared a conditioned medium (CM) using lyophilized MSC culture medium that contained the secretome of MSCs and applied this CM to the culture of neural stem cells (CM-NSCs) for the transplantation of PD model rats. Quantitative realtime PCR, Western blot, and immunocytochemistry were used to identify cell differentiation and expression of dopaminergic neuron-specific genes in vitro. Behavioral tests including rotational behavior and MWM training tests were also performed to assess the recovery. Our results indicated that combined treatment of CM and neural stem cell transplantation can significantly reduce apomorphine-induced rotational asymmetry and improve spatial learning ability. The CM-NSCs were able to differentiate into dopaminergic neurons in the ventral tegmental area (VTA) and medial forebrain bundle (MFB), and migrated around the lesion site. They showed a higher activity than untreated NSCs in cell survival, migration, and behavior improvement in the dopa-deficit rat model. These findings suggest that the neural stem cells treated with conditioned medium possess a great potential as a graft candidate for the treatment of Parkinson's disease.